Regulation and remodeling of microbial symbiosis in insect metamorphosis - Oishi, Sayumi; Moriyama, Minoru; Mizutani, Masaki; Futahashi, Ryo; Fukatsu, Takema (Proceedings of the National Academy of Sciences - PNAS, 2023)
Many insects are dependent on microbial mutualists, which are often harbored in specialized symbiotic organs. Upon metamorphosis, insect organs are drastically reorganized. What mechanism regulates the remodeling of the symbiotic organ upon metamorphosis? How does it affect the microbial symbiont therein? Here, we addressed these fundamental issues of symbiosis by experimentally manipulating insect metamorphosis. The stinkbug Plautia stali possesses a midgut symbiotic organ wherein an essential bacterial symbiont resides. By RNAi of master regulator genes for metamorphosis, Kr-h1 over nymphal traits and E93 over adult traits, we generated precocious adults and supernumerary nymphs of P. stali , thereby disentangling the effects of metamorphosis, growth level, developmental stage, and other factors on the symbiotic system. Upon metamorphosis, the symbiotic organ of P. stali was transformed from nymph type to adult type. The supernumerary nymphs and the precocious adults, respectively, developed nymph-type and adult-type symbiotic organs not only morphologically but also transcriptomically, uncovering that metamorphic remodeling of the symbiotic organ is under the control of the MEKRE93 pathway. Transcriptomic, cytological, and biochemical analyses unveiled that the structural and transcriptomic remodeling of the symbiotic organ toward adult emergence underpins its functional extension to food digestion in addition to the original role of symbiont retention for essential nutrient production. Notably, we found that the symbiotic bacteria in the adult-type symbiotic organ up-regulated genes for production of sulfur-containing essential amino acids, methionine and cysteine, that are rich in eggs and sperm, uncovering adult-specific symbiont functioning for host reproduction and highlighting intricate host–symbiont interactions associated with insect metamorphosis.